The impact of preschool programs in the achivement of first graders in elementary public schools of Lima - Cueto, Santiago (1999)
One of the major educational problems in Peru is the low level of efficiency attained in elementary schools. In this paper we analyze the impact of two types of preschool programs, Centros de Educación Inicial (CEI) and Programas No Escolarizados de Educación Inicial (PRONOEI). We carried out a retrospective survery in nine public schools in Lima that had a high repetition rate. Among children with preschool education at CEI the probability of getting a higher achievement increases in 25% in language and 22% in mathematics. Among children with preschool education at PRONOEI, the probability of obtaining a higher achievement increases in 15% in language and 17% in mathematics.